Population trends over 50 years of a Pied Imperial-Pigeon breeding colony on North Brook Island, a tropical Great Barrier Reef island, Australia. (1st March 2016) - Winter, John; Green, Dave; Thorsborne, Margaret; Parsons, Mark
Abstract: The Pied Imperial-Pigeon ( Ducula bicolor ) is a summer migrant to northern Australia, and nests colonially on many islands of the Great Barrier Reef, Queensland. Numbers are perceived to have declined as a result of large-scale shooting in the past and clearing of their mainland feeding grounds. To obtain evidence of any population changes, 1–10 counts were made each breeding season of the evening flight from the mainland to a nesting colony on North Brook Island. The counts began in 1965 and have continued for 50 years. The count represents one individual of a pair that visits the mainland to feed and returns in the evening. In the 1965–66 breeding season, the December count (the count used to compare years) was 4692 birds. Over the following three seasons, numbers declined to a low of 1451 birds in 1968–69; this decline was attributed to shooting of up to 1100 birds at a time. Large-scale shooting stopped in 1968 and was followed by a steady exponential increase ( y = 3370.4e 0.0908x in numbers over 23 years to 29 818 birds in the 1992–93 season. Numbers have fluctuated between ∼25 000 and 35 000 individuals over the following 18 years. A tropical cyclone of extreme intensity affected the pigeons' breeding site on North Brook Island and their mainland feeding areas in February 2011. In the following breeding season of 2011–12, numbers fell to 5311, but recovered to 21 088 in the 2012–13 season. The dramatic drop in numbers was attributed to the pigeons moving elsewhere for the 2011–12 season. It is predicted that the post-cyclonic number of 21 088 will take 4 years to recover to 30 000. The counts are a simple and somewhat coarse measure of population trends, but provide a population baseline for more sophisticated studies on the movements of pigeons and their responses to long-term changes in habitat and climate.